A multi-stakeholder collaborative approach to awareness, education and support needed in the haemophilia gene therapy patient journey – a report on insights from a European patient advisory board - O’Mahony Brian; Fletcher Simon; Baarslag Manuel; Khair Kate; Breederveld Daan; Jansen Nathalie; Pembroke Luke; Pinachyan Karen; Sivasubramaniyam Sujan (The Journal of Haemophilia Practice)
Gene therapy presents a potentially transformational approach to haemophilia management. The patient journey for gene therapy is unlike that for other haemophilia treatments, and its one-time, irreversible nature has led to broad agreement that informed shared decision-making is essential. Understanding the educational and support needs of people with haemophilia (PwH) who may consider or undergo gene therapy in the future is key to enabling this. A one-day patient advisory board was conducted with the aim of gaining insights on what education and support would enable PwH to have appropriate conversations with health care practitioners (HCPs) about gene therapy and participate in informed shared decision-making. The participants were 11 age-diverse men with severe haemophilia A or B, including six who had received gene therapy in phase 1-3 clinical trials. Two were members of a national patient organisation or a patient organisation leader. Participants agreed that informed shared decision-making was essential for gene therapy, but most felt the choice to have gene therapy would be limited by healthcare budgets and access arrangements. They identified key education needed by PwH to enable true informed decision-making, best delivered through a collaborative approach by patient organisations and HCPs. Eligibility criteria should be more widely shared within the community as part of general education around gene therapy. Gene therapy should be presented as one of a range of treatment options; understanding its risks, uncertainties and benefits is key to managing expectations and minimising treatment remorse. Awareness of how different factor levels impact bleeding tendency and frequency would be helpful, as success of gene therapy cannot be determined by factor activity alone. Other key educational needs included follow-up commitments, the role and potential side effects of corticosteroids or other immunosuppressants, impact on sense of identity, mental health, family planning, and managing bleeds after gene therapy. Teach-back could help ensure appropriate levels of understanding; psychological support could aid managing expectations. Peer-to-peer learning delivered across a variety of platforms, to share experiences of gene therapy and contextualise more ‘formal’ gene therapy education, was considered invaluable.